2016
DOI: 10.1590/1413-81232015217.06622015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of suggestive images of carotid artery calcifications on panoramic radiographs and its relationship with predisposing factors

Abstract: Prevalence of suggestive images of carotid artery calcifications on panoramic radiographs and its relationship with predisposing factorsPrevalência de imagens sugestivas de calcificações da artéria carótida em radiografias panorâmicas e sua relação com fatores predisponentes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
5
11
0
Order By: Relevance
“…However, no statistical significance was observed for the outcomes based on the association with sex. In accordance to the current study, Brito et al 8 (2016) also observed a higher prevalence of CAC in elder individuals (19.85% of patients were aged 61-80 years). Similarly, in this study, most CAC patients were aged >50 years (mean age, 58 years).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, no statistical significance was observed for the outcomes based on the association with sex. In accordance to the current study, Brito et al 8 (2016) also observed a higher prevalence of CAC in elder individuals (19.85% of patients were aged 61-80 years). Similarly, in this study, most CAC patients were aged >50 years (mean age, 58 years).…”
Section: Discussionsupporting
confidence: 92%
“…However, a statistically significant association was observed between age and prevalence of CAC (p < 0.05). Recently, Brito et al 8 (2016) detected CAC in 7.92% of the 505 panoramic radiographs analyzed. The authors found a higher prevalence of CAC in females (8.82%) than in males.…”
Section: Discussionmentioning
confidence: 99%
“…Khambet et al (8) reported values for sensitivity of 76% and specificity of 99% for DPR detecting calcified carotid artery atheromatous plaques. With this in mind we aimed to analyse the relation The risk factors for atherosclerosis, according to the literature, coincide with cardiovascular disease (13), such as increasing age (14), history of stroke, hypertension, diabetes, smoking, hypercholesterolemia (1,6,9,11,12,14), alcohol consumption (4,15) and obesity (16). Zheng et al (15) reported statistical significance between alcohol consumption in a population with atherosclerosis and cardiovascular accidents.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due, once again, to sample bias or recall bias. In the literature there is no consensus regarding this association, with some articles demonstrating a relationship between smoking and carotid atheromas detected by DPR (14) and others not reaching statistical significance (9).…”
Section: Discussionmentioning
confidence: 99%
“…To verify the presence of a potential carotid artery calcification, conventional anteroposterior projections (APPs) of the neck have been used to complement PRs. 1,10,11 However, carotid calcifications in APPs may be missed because of superimposition on the cervical…”
mentioning
confidence: 99%